Matching grants and economic activities among horticultural entrepreneurs: Long-term evidence from Rwanda. (February 2022) - Hossain, Marup; Mabiso, Athur; Garbero, Alessandra
Highlights: The impact of matching grants depends on who receives grants and whether they are invested in productive activities or not. This study shows that a grants intervention increases horticultural and total household income in Rwanda. The intervention also increases hired labor employment and asset holdings of beneficiary households. Long-term impacts on input expenditure and access to loans are not statistically significant. Overall results indicate that matching grants can have long-term positive effects on the livelihoods of smallholders.. Abstract: Matching grants can boost economic activities of small-scale producers by relaxing their credit or risk constraints. This study evaluates the impacts of a matching grants scheme targeted to horticultural enterprises in Rwanda. The intervention scores and endorses a business proposal if the proposal scores above the cut-off endorsement score. Following endorsement, if an entrepreneur receives and repays 50% of a loan taken for the proposed activity, the program matches the rest of the 50% of the loan. Using a fuzzy regression discontinuity design, we show that the overall intervention increases horticultural income of the households just above the endorsement cut-off compared to the households just below the cut-off. The intervention also increases wage and service income, labor employment, and asset holdings of the beneficiary households. Our results indicate that matching grants interventions can have long-term positive impacts on the livelihoods of small-scale producers.